Statelessness : a modern history - Siegelberg, Mira L., 1983- (Cambridge, Massachusetts : Harvard University Press, 2020)
"Two world wars left millions stranded in Europe. The collapse of empires and the rise of independent states in the twentieth century produced an unprecedented number of people without national belonging and with nowhere to go. Mira Siegelberg's innovative history weaves together ideas about law and politics, rights and citizenship, with the intimate plight of stateless persons, to explore how and why statelessness compelled a new understanding of the international order in the twentieth century and beyond. In the years following the First World War, the legal category of statelessness generated novel visions of cosmopolitan political and legal organization and challenged efforts to limit the boundaries of national membership and international authority. By linking the emergence of mass statelessness to a revolution in legal consciousness, Siegelberg shows how the rights regime created after the Second World War ultimately empowered the territorial state as the source of protection and rights, against alternative political configurations. Today, more than twelve million people are stateless and millions more belong to categories of recent invention, including refugees and asylum seekers. As Statelessness makes clear, understanding the ideological origins of the international agreements that define approaches to citizenship and non-citizenship can better equip us to confront the dilemmas of political structure and authority at a global scale"--
Introduction: The question of questions -- From legal fiction to legal reality -- Post-imperial states of statelessness -- Post-imperial foundations of political order -- The reality of norms -- Conditions of world order -- Nationalizing the international -- Conclusion: States of statelessness.
Include bibliographical references and index.
Trim Education
Keywords: Statelessness; Stateless persons